An inertial two-phase model of wax transport in a pipeline during pigging operations. (September 2017) - Boghi, Andrea; Brown, Lloyd; Sawko, Robert; Thompson, Christopher P.
Highlights: This is a 3D modeling study on the wax removal from pipeline wall. The results of the present 3D numerical investigation reveal the limits of the 1D modeling. The results show that the temperature has the greatest influence in determining the shape of the moving dune. The deposition of the wax particles is affected by a whirling motion. The results show that the non-uniform axial velocity field causes the dune to advance further than the pig. Abstract: Pig in pipelines performs operations for cleaning the pipe interior and internal inspection. In the past few years many 1D models have been developed to simulate the process because of their reduced computational cost; however, they rely on simplifications which are not always valid. In this paper, the results of a three-dimensional (3D) numerical investigation of the interaction between a waxy-oil and a dynamic sealing pig in a pipeline are presented. The results are obtained at a reduced computational cost by using a moving frame of reference, and an "injection" boundary condition for the wax deposited on the wall. The effect of the temperature and the wax particles' size has been investigated. The 3D results show the structure assumed by the debris field in front of the pig. In particular, a lubrication region at the bottom of the pipe, whose dimensions are temperature dependent, is shown. This information cannot be deduced from 1D modeling. The influence of the oil on the mixture viscosity and the internal bed dynamics are discussed. This work provides insights into the interaction between the debris field in front of the pig and pipeline hydraulics.